Análise da diversidade genética de Astyanax lacustris do Rio Sapucaí-Mirim: ações efetivas como forma mitigadora na implantação das PCH'S - Freitas, Gabriela Idaline (2022)
Brazil is a country with great hydroelectric potential, so there are several dams that are classified into Large Hydroelectric Plants (LHPs) or Small Hydroelectric Plants (SHPs). The Sapucaí-Mirim river, tributary of the Upper Paraná basin, is one of many that have SHPs along its length. The anthropic impact caused by these dams directly interferes with natural populations of the present ichthyofauna. That way, studies of genetic diversity become indispensable, helping to implement mitigating measures. Microsatellite molecular markers are a tool widely used in genetic diversity studies, because off their codominance, abundance in the eukaryote genome and degree of polymorphism. Thereby, the present study used microsatellite markers to analyze the genetic diversity of natural populations of A. lacustris in the years 2013 and 2021, with the objective of verifying the impact that these dams have on natural populations. Seven microsatellite loci pre-described in the literature were applied, and their results were later analyzed by computer programs. In general, both populations showed a high genetic diversity. The results obtained can be explained by the presence of mitigating measures in the region, by the fact that the SHPs have been built recently, or by the great adaptive capacity of the species used.